異常気象をもたらす大気の大波「北極振動」と2010年猛暑の関係 - 立花, 義裕; Yoshihiro, TACHIBANA; 大富, 裕里子; Yuriko, OTOMI; 中村, 哲; Tetsu, NAKAMURA (三重大学大学院生物資源学研究科, 2012)
application/pdf In 2010, the Northern Hemisphere, in particular Russia and Japan, experienced an abnormally hot summer characterized by record-breaking warm temperatures and associated with a strongly positive Arctic Oscillation （AO）, that is, low pressure in the Arctic and high pressure in the midlatitudes. In contrast, the AO index the previous winter and spring （2009/2010） was record-breaking negative. The AO polarity reversal that began in summer 2010 can explain the abnormally hot summer. The AO-related summertime tropical oceanic warm temperature anomaly might have been a remote cause of the formation of blocking highs in the Europe, thus amplifying the positive summertime AO. Understanding of this interseasonal linkage may aid in the long-term prediction of such abnormal summer events. departmental bulletin paper